NHC‐Containing Manganese(I) Electrocatalysts for the Two‐Electron Reduction of CO2. Issue 20 (2nd April 2014) - Agarwal, Jay; Shaw, Travis W.; Stanton, Charles J.; Majetich, George F.; Bocarsly, Andrew B.; Schaefer, Henry F.
Abstract: The synthesis and characterization of the first catalytic manganese N‐heterocyclic carbene complexes are reported: MnBr( N ‐methyl‐ N ′‐2‐pyridylbenzimidazol‐2‐ylidine)(CO)3 and MnBr( N ‐methyl‐ N ′‐2‐pyridylimidazol‐2‐ylidine)(CO)3 . Both new species mediate the reduction of CO2 to CO following two‐electron reduction of the Mn I center, as observed with preparative scale electrolysis and verified with 13 CO2 . The two‐electron reduction of these species occurs at a single potential, rather than in two sequential steps separated by hundreds of millivolts, as is the case for previously reported MnBr(2, 2′‐bipyridine)(CO)3 . Catalytic current enhancement is observed at voltages similar to MnBr(2, 2′‐bipyridine)(CO)3 . Abstract : Catalytic manganese N‐heterocyclic carbene complexes have been synthesized and characterized: [MnBrL(CO)3 ] (see scheme; L= N ‐methyl‐ N ′‐2‐pyridylbenzimidazol‐2‐ylidine or N ‐methyl‐ N ′‐2‐pyridylimidazol‐2‐ylidine). Both species mediate the reduction of CO2 to CO following two‐electron reduction of the Mn I center at a single potential, as observed with preparative scale electrolysis and verified with 13 CO2 .